Optimalisasi Wakaf Uang Berbasis Digital dalam Meningkatkan Inklusivitas Filantropi Islam di Yayasan Edukasi Wakaf Indonesia - Fajri, Fajriansyah Abdillah; Fajriansyah Abdillah; Fatkhur Rohman Albanjari; Nugraheni Fitroh Rezqi Syakarna (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to determine the optimization of digital-based cash waqf at the Education Waqf Foundation of Indonesia. Currently, digital development is important for waqf institutions because it facilitates inclusive access to all levels of society. The research methodology is a descriptive qualitative approach. The types of research data include primary data and secondary data. Primary data collection techniques were obtained through informant interviews with institutional leaders, cash waqf managers, digital administrators, waqf nadzirs working with endowments, and waqifs. Secondary data is obtained through literature studies sourced from Indonesian Waqf Board, the Institute's website and information related to cash waqf obtained through electronic media. The data analysis technique uses field data analysis, namely data reduction, data presentation, and concluding. The results showed that the Education Waqf Foundation of Indonesia in managing cash waqf funds is more effective and on target when done through digital. Digital-based cash waqf activities include the process of raising funds, managing waqf financial management, and distributing waqf funds. Digital-based cash waqf activities become more efficient, transparent and accountable, creating trust at all levels of society. Through the Pasifamal.id platform, all information related to waqf is easily accessible. This increases public trust and participation in waqf. Digital-based monitoring and reporting helps ensure that waqf funds are optimally used for their intended purpose.